Design and analysis of a flywheel energy storage system fed by matrix converter as a dynamic voltage restorer - Aydogmus, Omur; Boztas, Gullu; Celikel, Resat (Pergamon-Elsevier Science Ltd, 2022)
This paper presents design, optimization, and analysis of a flywheel energy storage system (FESS) used as a Dynamic Voltage Restorer (DVR). The first purpose of the study was to design a flywheel with a natural resonance frequency outside the operating frequency range of the FESS. The second purpose of the study was to show that a matrix converter structure can be used for a FESS. The matrix converter can bidi-rectionally convert the power between the grid and the flywheel due to its natural property. The matrix converter needs a special motor/generator design, because of the voltage utilization ratio of the matrix converter. Therefore, a Permanent Magnet Synchronous Motor (PMSM) being compatible with the matrix converter voltage level was designed and optimized as the third purpose of this study. The motor was optimized to achieve low torque ripple and as high torque as possible by using multi-objective optimization algorithm. Input/output voltages of the FESS are analyzed for grid interruption and 50% voltage sag operation conditions. The frequency analysis study was performed by using SolidWorks, the PMSM was designed and optimized by using MAGNET-Infolytica, and all the other results are performed by using MATLAB-Simscape. (c) 2021 Elsevier Ltd. All rights reserved.
Keywords: Dynamic voltage restorer; Electric motor design; Energy storage; Flywheel; Matrix converter